The compleat Ankh-Morpork - Pratchett, Terry (Doubleday, 2014)
"A brand-new street directory of Discworld city Ankh-Morpork complete with a beautifully illustrated pull-out map. This is the city celebrated in Terry Pratchett's bestselling Discworld series as you've never seen it before. A stunning map and comprehensive street directory covering each and every district from Unseen University to the Shades, major landmarks like the Patrician's Palace to little-known, er, nooks like Dwarf Bread Museum in Whirligig Alley. See the notorious establishments and famous streets along which so many heroes have walked, in some cases quite hurriedly. As leading Ankh-Morpork entrepreneur CMOT Dibbler would say, 'A nip at any price -- and that's cutting our own throat. Well, close."--